2013
DOI: 10.1680/macr.12.00015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano-calcium carbonate on early-age properties of ultra-high-performance concrete

Abstract: In this study, the effects of nano-calcium carbonate (CaCO3) addition on the early-age properties of ultra-high-performance concrete cured at simulated cold and normal field conditions were investigated. The nano-CaCO3 was added at rates of 0, 2·5, 5, 10 and 15% as a partial volume replacement for cement. Similar mixtures incorporating chloride- and non-chloride-based accelerating admixtures were also tested for comparison. Results indicate the high potential of nano-CaCO3 to accelerate the setting and hardeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(65 citation statements)
references
References 31 publications
0
58
0
Order By: Relevance
“…An increasing number of studies on this issue have been reported in the last few years. Camiletti, Soliman, and Nehdi (2013) tested the effects of NCa on the early-age properties of ultra-high-performance concrete (UHPC) with addition of NCa at 0, 2.5, 5, 10 and 15% by weight of cement.…”
Section: European Journal Of Environmental and Civil Engineering 15mentioning
confidence: 99%
“…An increasing number of studies on this issue have been reported in the last few years. Camiletti, Soliman, and Nehdi (2013) tested the effects of NCa on the early-age properties of ultra-high-performance concrete (UHPC) with addition of NCa at 0, 2.5, 5, 10 and 15% by weight of cement.…”
Section: European Journal Of Environmental and Civil Engineering 15mentioning
confidence: 99%
“…Some authors observed that NPs improve both fluidity and workability as they influence the process of hydration and fill the empty spaces. 21,22 In addition, NPs provide these effects even when used at low levels. 23 The Ag NPs show high antibacterial efficacy and low toxicity to humans, 24,25 being studied in various dental applications, such as restorative material, 26 retrosealer, 27 and dental implants.…”
Section: -15mentioning
confidence: 99%
“…In recent years, nano-CaCO 3 has been introduced in concrete [18], and some studies have suggested a potential benefit of physical properties of nano-CaCO 3 on the development of cementitious system [19][20][21][22][23][24]. However, it is believed that the most important challenge in the nanocomposite research is to disperse properly the nanomaterials into the matrix [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to the sophisticated surface structures of nanomicron composite particles, it can have a signi cant e ect on the hydration and microstructure of cementitious materials. Camiletti et al [20] found that nano-CaCO 3 accelerates the setting and hardening process of ultra-high-performance concrete through providing nucleation sites, increasing contact points, and increasing the e ective water-to-cement ratio. Yang et al [16] also believes that nano-CaCO 3 particles on the surface of LS can act as heterogeneous nuclei for cement paste, making the size of calcium hydroxide crystals smaller, leading to a denser microstructure.…”
Section: Introductionmentioning
confidence: 99%